Modern spatiotemporal geostatistics - Christakos, George (Dover earth science, 2012)
" This introductory scholarly treatment explores the fundamentals of modern geostatistics, a group of spatiotemporal concepts and methods related to the advancement of the epistemic status of stochastic data analysis. Christakos considers the role of geostatistics in improved mathematical models of scientific mapping, and focuses on the Bayesian maximum entropy approach for studying spatiotemporal distributions of natural variables. 2000 edition"--